2004
DOI: 10.1086/422848
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in HIV‐Seropositive versus ‐Seronegative Persons in the Era of Highly Active Antiretroviral Therapy: Implications for When to Initiate Therapy

Abstract: Survival of HIV-seropositive participants receiving HAART approximated that of HIV-seronegative participants only when therapy was given at CD4 cell counts > 350 cells/microL. These data, restricted to IDUs, suggest initiating or switching to HAART at higher CD4 cell levels than are currently recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 41 publications
3
46
1
1
Order By: Relevance
“…Few studies have compared survival among HIV-infected IDUs in the HAART era with an epidemiologically appropriate comparison group of HIV-uninfected IDUs [18,19]; the present study's findings are consistent with these prior data. Kohli et al [18] reported a 50% reduction in the mortality rate from 1996 to 2001 among a large cohort of HIV-infected and HIVuninfected IDUs who were recruited from methadone maintenance programs in the Bronx, New York.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Few studies have compared survival among HIV-infected IDUs in the HAART era with an epidemiologically appropriate comparison group of HIV-uninfected IDUs [18,19]; the present study's findings are consistent with these prior data. Kohli et al [18] reported a 50% reduction in the mortality rate from 1996 to 2001 among a large cohort of HIV-infected and HIVuninfected IDUs who were recruited from methadone maintenance programs in the Bronx, New York.…”
supporting
confidence: 89%
“…Furthermore, access to low-threshold methadone treatment programs like those in Barcelona is more limited in the United States [22]. Despite the apparent differences in the access to care and the variation in the stage of HIV disease, the mortality rates among both HIV-infected and HIV-uninfected IDUs observed in the HAART era in the study by Muga et al [1] were very comparable to those among IDUs in studies from urban US cities [18,19].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The results are based on a sample of injection drug users who had CD4 þ cell counts below 200/ll; this limited inferences to the observed impact of HAART on those with advanced immunosuppression. While this was done to preserve comparability over the length of the study period, so as to incorporate observations when treatment was recommended primarily for those with advanced immunosuppression, data from our cohort on those with CD4 þ cell counts above 200/ll have been published elsewhere (39). Another possible limitation involves the use of self-reports and the concern over responding in a socially desirable manner.…”
Section: Discussionmentioning
confidence: 99%
“…On some occasions the professionals prefer to delay the shift from non-HAART to HAART regimes until the patient achieves adherence or until he or she controls his or her addiction, 11,26,28 which compromises their prognosis. 29 It has been shown that once HAART is initiated, the response is similar among injecting drug users and noninjecting drug users. 2,30 However, most authors have described worse virological responses 31 and, in general, a higher risk of progression to AIDS and death among IDUs.…”
Section: Rodríguez-arenas Et Al 718mentioning
confidence: 99%